Dietary patterns and the risk of obesity, type 2 diabetes mellitus, cardiovascular diseases, asthma, and neurodegenerative diseases. Issue 2 (22nd January 2018) - Medina-Remón, Alexander; Kirwan, Richard; Lamuela-Raventós, Rosa M.; Estruch, Ramón
ABSTRACT: Diet and lifestyle play a significant role in the development chronic diseases; however the full complexity of this relationship is not yet understood. Dietary pattern investigation, which reflects the complexity of dietary intake, has emerged as an alternative and complementary approach for examining the association between diet and chronic diseases. Literature on this association has largely focused on individual nutrients, with conflicting outcomes, but individuals consume a combination of foods from many groups that form dietary patterns. Our objective was to systematically review the current findings on the effects of dietary patterns on chronic diseases. In this review, we describe and discuss the relationships between dietary patterns, such as the Mediterranean, the Dietary Approach to Stop Hypertension, Prudent, Seventh-day Adventists, and Western, with risk of obesity, type-2 diabetes mellitus, cardiovascular diseases, asthma, and neurodegenearive diseases. Evidence is increasing from both observational and clinical studies that plant-based dietary patterns, which are rich in fruits, vegetables, and whole grains, are valuable in preventing various chronic diseases, whereas a diet high in red and processed meat, refined grains and added sugar seems to increase said risk. Dietary pattern analysis might be especially valuable to the development and evaluation of food-based dietary guidelines.